Breaking barriers in education: leveraging 3E approach and technology to foster inclusion for SEN students - Videla, Ronnie; Parada, Francisco J.; Aros, May Britt; Ramírez, Paola; Sarzosa, Alexis; Jorquera, Daniela; Palma, Camila; Trujillo, Alline; Ibacache, David; González, María Jesús; Velásquez, Andri; Molina, Karelia; et al. (Frontiers in Education, 2025)
Advances in embodied design highlight the interconnection between the brain, body, and environment in shaping learning experiences, emphasizing the potential of multimodal perception in enriched sociomaterial and technological contexts. Despite growing evidence in this area, traditional educational systems remain anchored in transmissive and cognitivist models, perpetuating barriers to equitable learning, particularly for students with special educational needs (SEN), such as Attention Deficit Hyperactivity Disorder (ADHD), Autism Spectrum Disorder (ASD), and Specific Learning Disabilities (SLD). In response to these challenges, post-cognitivist frameworks, including embodied, enactive, and environmentally scaffolded cognition (3E) as well as SpEED (Special Education Embodied Design), provide essential foundations for rethinking inclusive educational design. This perspective article explores the role of active teaching methodologies and innovative technologies in shaping a holistic framework to support inclusive learning design. This framework leverages immersive technologies, mobile applications, and artificial intelligence to scaffold multimodal learning experiences that meet the diverse needs of students with SEN. Through a proof-of-concept based on illustrative cases, this article presents a theoretical contribution to guide the design of inclusive and technology-supported learning environments aligned with the 3E approach, fostering engagement, equity, and personalized learning for students with SEN.